Running anatomy - Puleo, Joe; Milroy, Patrick (Human Kinetics, 2010)
See what it takes to maximize running strength, speed, and endurance! Running Anatomy will show you how to improve your performance by increasing muscular strength, optimizing the efficiency of your running motion, and minimizing your risk for injury. Running Anatomy features 50 of the most effective strength exercises for runners, each with clear, step-by-step descriptions and full-color anatomical illustrations highlighting the muscles in action. But you'll find much more than exercises-you'll also see their results. Running Anatomy places you in the action, fundamentally linking each exercise to running performance. You'll see how to strengthen muscles, reduce injury, and improve gait efficiency for faster times and more fluid runs. Running Anatomy will prepare you for any challenge that comes your way. You'll find exercises for varying terrains and speeds, from hill running to off-road running and from sprints to marathons. Plus you'll learn how to evaluate and rehabilitate the most common injuries that runners face, including lower-back pain, knee aches and strains, and torn muscles and tendons. Whether you're a fitness runner looking to conquer hills with more speed or strength or a competitive runner looking for that extra bit of performance and a finishing kick, Running Anatomy will ensure that you're ready to deliver your personal best.